Os objetos educacionais digitais de um livro didático digital de língua portuguesa: um estudo sobre as práticas de leitura - Alcantara, Fabiana Silva De Paula [UNIFESP] (2020)
This master’s dissertation is research into the Applied Linguistics fields and aims to contribute to the analysis of Digital Learning Objects (DLOs) of a Portuguese-language-electronic textbook, designed for the ninth grade of Elementary School, approved in the PNLD National Textbook Plan 2017. To understand how the textbook is planned, more specifically the various approaches of the DLOs activities, a documentary analysis was performed to investigate the contents, the theoretical explanations and the exercises found in the DLOs. DLOs came about with the PNLD 2014, and they made available on DVD for the PNLD 2017, the publishers launched a printed version and an electronic version of this textbook, and both versions must have multimedia features included. The latest version would also have DLOs included in its content. The textbook constitutes the major teaching-learning material in the classrooms, and with the advent of the new technologies (NT), it has received a new configuration to suit the requirements of the teaching-learning process. Since the text has changed, new ways of thinking literacy have aroused. Hence, there is a need for reshaping of literacies practices. Thus, it is important to understand the impact on these changes in the Portuguese language teaching-learning process, taking into consideration this research aims; we analyzed how the approach of these new literacies take place and how they happen in the DLOs. We verified the multimodal resources present in these DLOs. In this regard, a theoretical survey was conducted which allowed us to set a parameter on the characteristics of these digital resources. The survey also enabled us to comprehend the categories of analysis and the element and characteristics in this material we should focus on. This research concerned to analyze the only five DLOs present on the 09th. Edition of the textbook’ Projeto Teláris collection, written by Borgatto, Bertin and Marchezi (2015). This Portuguese-language textbook, designed for elementary school II, was the only approved collection ranked by PNLD 2017. Our analysis of this study concludes that the DLOs’ resources are complementary to the theoretical studies inducted in the textbook. They consist of videos and infographics, many of them have motionless content and has no interactivity. They explore the multiple semiosis that comes from digital environments. Regarding the new literacies, the DLOs do not favor the collaborative practices of the new literacies. The analysis demonstrates that this work is still superficial concerning these practices.